Precommercial thinning in naturally regenerated Scots pine stands in northern Finland. - Ruha, Tommi; Varmola, Martti (The Finnish Society of Forest Science and The Finnish Forest Research Institute, 2009)
The effects of precommercial thinning on the quantity and external quality of young Scots pine stands were examined over two 10-year periods in an experiment comprising five stands growing on sub-dry sites in Finnish Lapland, northern Finland. The thinning treatments applied resulted in stand densities of 625, 1111, 1600, 2500 and 4444 stems ha–1 and a no-treatment, unthinned plot with a randomised block lay-out of two or tree replications in each stand. The dominant height of the stands varied between 4 and 8 m at the time of thinning. The trees reacted only slightly to the increase in growing space during the first ten years following precommercial thinning. During the second 10-year period, increased growing space was reflected more clearly in diameter and volume increment. These reactions were more evident in stands thinned at an early stage. The increment of the thinnest 100–200 trees ha–1 in each treatment was poor. The results showed that when the main principle in precommercial thinning is to achieve even spacing, the remaining smallest trees fail to react positively to the increase in growing space. In other words, the target of precommercial thinning should be to concentrate the increment on the tallest trees, even though they are located in groups. The external quality of the trees in stands where precommercial thinning was carried out at a later stage was high, and the diameter of the thickest branch along the butt log remained under 20 mm. Branch diameter was greater in stands thinned at an early stage. The effect of precommercial thinning on branch diameter when comparing the extreme treatments averaged 5 mm. When the aim of stand management is to combine high quality and good yield in naturally regenerated Scots pine stands in northern Finland, precommercial thinning should not be carried out before the dominant height of 7–8 m. The intensity of precommercial thinning depends on the yield targets of the first commercial thinning. A spacing of 2500 stems ha–1 satisfies the requirements of both high ...